Business games as a method of training information security specialists - Шиліна, Наталія Євгеніївна; Копитін, Юрій Вікторович (Ukrainian Information Security Research Journal, 2013)
Providing an adequate level of information security is directly dependent on quality training of future specialists, the level of implementation and use of innovative teaching, infocommunication technologies and information culture. The current state of training specialists of information security industry indicates that the current requirements for skills and experience of students do not consistent with are necessary for building an effective information security management system of the organization. The paper disclosed methodology of business games for training specialists in information security industry. The described method of training will allow students better understand the material, develop their ability in solving the problem of information security, understand some or other questions of information security, and learn to work in teams. The business games help to ensure the future information security professionals necessary theoretical knowledge and practical skills in modern methods and tools of information security.